Victor Feather, 1947 (1947)
1947 1945-1960 "Victor Feather, 1947" [HFR0139], 1947 Victor Feather joined the TUC Staff in 1937, became Assistant Secretary in 1947 and went on to become General Secretary 1969-1973. In this article from the Birmingham Trades Council Journal for August 1947, he refers to the post war fuel and economic crisis.